Pesticide Safety and Personal Protective Equipment for Citrus Grove Workers - Brian Boman; Darren Cole; Steve Futch; Ward Gunter; Jack W. Hebb; P. Chris Wilson (EDIS)
Revised! AE244, an 11-page fact sheet by Brian Boman, Darren Cole, Steve Futch, Ward Gunter, Jack Hebb, and Chris Wilson, is part of the Best Management Practices (BMPs) for Citrus Grove Workers series. It provides information for citrus grove workers about toxicity and effects of exposure to pesticides and personal protective equipment. Includes two quizzes and references. Published by the UF Department of Agricultural and Biological Engineering, February 2009.